114k views
7 votes
What is the solution to the following question

What is the solution to the following question-example-1

1 Answer

6 votes

Answer:

3

Explanation:

2(x + 1) = 3(5 - x) + 2

Distribute,

2(x + 1) = 3(5 - x) + 2

2x + 2 = 3(5 - x) + 2

Rearrange terms,

2x + 2 = 3(5 - x) + 2

2x + 2 = 3(-x + 5) + 2

Distribute,

2x + 2 = 3(-x + 5) + 2

2x + 2 = -3x + 15 + 2

Add the numbers,

2x + 2 = -3x + 15 + 2

2x + 2 = -3x + 17

Subtract 2 from both sides,

2x + 2 = -3x + 17

2x + 2 - 2 = -3x + 17 - 2

2x = -3x + 17 - 2

2x = -3x + 15

Add 3x to both sides,

2x = -3x + 15

2x + 3x = -3x + 3x + 15

5x = -3x + 3x + 15

5x = 15

Divide both sides by the same factor (15),

5x = 15

5x/5 = 15/5

x = 15/5

x = 3

Hence, the answer is 3.

User Manuna
by
6.3k points